Robust Anion‐Shielding Metal‐Organic Frameworks Based Composite Interlayers To Achieve Uniform Li Deposition for Stable Li‐Metal Anode. Issue 3 (2nd February 2022) - Li, Chuanfu; Lu, Ruichao; Amin, Kamran; Zhang, Binbin; Liu, Hao; Zheng, Wei; Guo, Jinze; Du, Peiyao; Mao, Lijuan; Lu, Xiaoquan; Wei, Zhixiang
Abstract: Lithium (Li) metal is one of the most promising anode candidates for next‐generation rechargeable batteries with a high energy density because of its high theoretical specific capacity and low reduction potential. However, the growth of lithium dendrites causes intolerable safety risks and poor electrochemical performances. Limiting the migration of anions near the Li‐metal anode is regarded as an effective strategy to achieve uniform Li deposition and thus suppress the dendritic growth. Here, a metal‐organic frameworks based polyvinylidene fluoride‐hexafluoropropylene copolymer composite interlayer is designed and prepared through an in situ heat‐assisted method. Being guided and assisted by the anion‐shielded composite interlayer, a homogenous Li‐ion flux as well as a high Li‐ion transference number are achieved, which promotes the uniform and stable lithium deposition. At the same time, the robust composite interlayer is expected to suppress the growth of Li dendrites by its intrinsically high modulus (≈2.49 GPa). As a result, symmetrical batteries exhibit excellent cyclic stability for over 1600 h with functional composite interlayer. Furthermore, full cells with a commercial lithium iron phosphate cathode demonstrate remarkably enhanced cycling performance with a satisfying capacity retention of 96 % after 500 cycles. This work provides an effective strategy for the design and fabrication of functional composite interlayers to realize stable lithium metal anodes. Abstract : A robust anion‐shielded metal‐organic framework ZIF‐8 based mixed matrix interlayer (MMIs) ZIF‐8@PVDF‐HFP on the Li‐metal anode can achieve high‐performance Li‐metal anodes. The MMIs can obtain a homogenous Li‐ion flux as well as a high Li‐ion transference number, and thus promote uniform Li deposition and suppress the dendritic growth. The MMIs‐modified Li/Li symmetric batteries maintain long cyclic life (>1600 h).